1115 Chronic traumatic encephalopathy in retired footballers with dementia. (1st December 2017) - Ling, Helen; Morris, Huw; Neal, James; Lees, Andrew; Hardy, John; Hotlon, Janice; Revesz, Tamas; Williams, Don
Abstract : Chronic traumatic encephalopathy (CTE) is a potential neurodegenerative cause of dementia and motor impairments in individuals with past exposure to repetitive head impacts. From 1980 to 2010, 2014 retired football (soccer) players with dementia were followed up regularly until death. All were skilled headers of the ball; 13 were professional and 1 was a committed amateur, and they played football for an average of 26 years. Concussion was reported in six cases only limiting to one episode each. Progressive cognitive impairment started at an average age of 63.6 years with an average survival of 10 years. Consent for post-mortem was obtained in six cases. The pathological diagnosis of CTE was established in 4 of the 6 post-mortem cases and is probably related to their past prolonged exposure to repetitive head impacts from head-to-player collisions and heading the ball thousands of time throughout their careers. Concomitant pathologies were common, including Alzheimer's disease (n=6), TDP-43 (n=6), cerebral amyloid angiopathy (n=5). Football is the most popular sport in the world and the potential link between repetitive head impacts from playing football and CTE is of considerable public health interest. Our findings support the need for further large scale case-control studies to identify at risk groups of footballers which will justify for the implementation of protective strategies.